SENGKARUT KEPAILITAN PERUSAHAAN PERASURANSIAN DI INDONESIA : PERLINDUNGAN HUKUM PEMEGANG POLIS ASURANSI DALAM KEPAILITAN PERUSAHAAN ASURANSI JIWA - Putu Eka Trisna Dewi (Jurnal Yustitia, 2020)
Business activities are activities that are closely related to risk. The insurance company is one of the companies that carry out activities in the field of insurance. Insurance companies specifically life insurance companies usually become third-party risk transfer, but that does not mean insurance companies do not have risks.. This research is a normative legal research with literature study and statute approach. One problem that often occurs life insurance companies is a case of default. Against the state of such insurance companies, bankruptcy is the next step. Bankruptcy insurance companies are not as easy as bankruptcy companies in general.